2019
DOI: 10.3390/risks7030084
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Conditions of High Financial Risk in the SME Sector

Abstract: The sector of SME is the major force for the national economic and social development. Financial risk is one of the key threats to the activity of small and medium enterprises. The most common manifestation of the financial risk of SMEs is difficulty in financing the business and lack of funds for development. Banks are unwilling to grant loans to such companies. Moreover, it is the rising operating costs that cause shrinking profits, which may result in corporate debt, difficulty in debt repayment, and conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…The effective risk management in SMEs is deciding to a large extent whether they are fit to survive in the market and contributes to the development not only of a company but also its market and social environment. At the same time, note the appropriate risk management requires a certain degree of risk perception in a given business environment, risk identification, planning and alignment of preventive measures, or risk management systems ( Slusarczyk & Grondys, 2019). The results show that financial risk has the most significant positive impact on a perception of the future (path coefficient -PC ¼ 0.16).…”
Section: Discussionmentioning
confidence: 95%
“…The effective risk management in SMEs is deciding to a large extent whether they are fit to survive in the market and contributes to the development not only of a company but also its market and social environment. At the same time, note the appropriate risk management requires a certain degree of risk perception in a given business environment, risk identification, planning and alignment of preventive measures, or risk management systems ( Slusarczyk & Grondys, 2019). The results show that financial risk has the most significant positive impact on a perception of the future (path coefficient -PC ¼ 0.16).…”
Section: Discussionmentioning
confidence: 95%
“…Many SMEs do not apply risk management practices due to their limited resources, even though competent risk management reduces the risk of insufficient profit. Very often, SME owners do not pay attention to the implementation and development of risk management strategies and demonstrate an informal approach to their management, which significantly affects the level of generated profit (Ślusarczyk & Grondys, 2019). Hence, the approach SMEs adopted towards risk management is thus dependent on their attitude to sustainable development.…”
Section: Management Of Financial Risk In Smesmentioning
confidence: 99%
“…The growth and development of SMEs partly depend on how financial risk management is well-practiced in the organization (Belas et al, 2015b;Dobrovič et al, 2019;Belas et al, 2020), as it has been identified, the poor capital structure of SMEs is a major reason for their exposure to financial risks (Zhao & Zeng, 2014). With the business expansion and active decision-making, the cost of acquiring new technologies, processes, and supplies is the largest source of financial risk (Ślusarczyk & Grondys, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it can result in the rising operating costs, rising corporate debt, difficulty in debt repayment, and consequently, high financial risk (Korcsmáros & Šimova, 2018). It was indicated that both the internationalization of the company and the ability to manage risk are the only factors that affect a high level of risk of low income (Ślusarczyk & Grondys, 2019). The authors conclude that due to special characteristics of SMEs, the identification and measurement of SME financial risk should be different from the large ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Ślusarczyk and Grondys (2019), any company, not only in the SME sector, should deal with the task of managing financial risk in the manner that will bring greater benefits to it. Based on the authors' opinions, an important part of the financial risk of SMEs CENTRAL EUROPEAN BUSINESS REVIEW is a higher share of foreign capital in their financing.…”
Section: Literature Reviewmentioning
confidence: 99%